Impact of Small Scale Storage and Intelligent Scheduling Strategy on Cost Effective and Voltage Secure Operation of Wind+PV+Thermal Hybrid System. Issue 1 (3rd November 2022) - Dauda, Alpesh Kumar; Panda, Ambarish
Abstract: The growing concern on climate change and environmental pollution has created enormous pressure on shifting the generation toward cleaner and environmental friendly sources. Among different clean energy producers, wind power and solar photovoltaic (PV) systems are the most attractive ones due to their abundant availability, substantial power production capability, and cost effective attributes. But, their intermittent availability makes the system operation extremely vulnerable. Therefore, optimum utilization of renewable energy in hybrid power system (HPS) may not be achievable without the integration of energy storage facilities. In this context, integration of battery energy storage (BES) systems with Wind+PV+Thermal (WPT) hybrid configuration is considered in this work to meet the sudden and short term disharmony between actual and available renewable power output. Moreover, to maintain a secure system voltage of the WPT+BES system, the impact of reactive power ( Q ) capability of doubly fed induction generator has also been analyzed. The scheduling problem of the proposed HPS is solved by formulating in an optimization framework. Intelligent technique is applied to evaluate the optimal operational paradigm at multiple percentage of renewable energy penetration scenarios at which the proposed HPS may operate in a voltage secure and cost effective manner. The validation of the proposed operating strategy on the comparative performance evaluation of WPT and WPT+BES systems is portrayed on IEEE30 bus benchmark power system configuration. Abstract : This work presents a comparative analysis in terms of achieving economic and voltage secure operation among WPT (Wind+PV+Thermal) and WPT+battery energy storage hybrid power configurations in a constrained optimization environment. To make the analysis robust, system operation at normal, random disrupted events, and at variable penetrations of renewable energy scenarios are carried out.